2022
DOI: 10.1071/fp22177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought stress on wheat (Triticum durum) growth and metabolism: insight from GABA shunt, reactive oxygen species and dehydrin genes expression

Abstract: Activation of γ-aminobutyric acid (GABA) shunt pathway and upregulation of dehydrins are involved in metabolic homeostasis and protective mechanisms against drought stress. Seed germination percentage, seedling growth, levels of GABA, alanine, glutamate, malondialdehyde (MDA), and the expression of glutamate decarboxylase (GAD) and dehydrin (dhn and wcor) genes were examined in post-germination and seedlings of four durum wheat (Triticum durum L.) cultivars in response to water holding capacity levels (80%, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…The overexpression of dehydrins in various plant species, including crops like wheat and ornamental plants like Ammopiptanthus nanus, has been shown to enhance tolerance to drought, salt, and cold stresses. This indicates that the increased expression of dehydrins confers enhanced stress tolerance in different plant species across different contexts [42,57]. The silencing of CaDHNs has been observed to decrease the tolerance of plants to cold, salt, and drought stresses [17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The overexpression of dehydrins in various plant species, including crops like wheat and ornamental plants like Ammopiptanthus nanus, has been shown to enhance tolerance to drought, salt, and cold stresses. This indicates that the increased expression of dehydrins confers enhanced stress tolerance in different plant species across different contexts [42,57]. The silencing of CaDHNs has been observed to decrease the tolerance of plants to cold, salt, and drought stresses [17].…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of dehydrins enhances drought, chilling, and salt tolerance [40,41]. In plant cells, dehydrins can maintain cell stabilization and homeostasis They help prevent cell dehydration, eliminate free radicals, protect macromolecules, and bind metal ions [37,42,43]. Li et al found that dehydrin MtCAS31, which functions as a cargo receptor, participates in autophagy degradation in response to drought stress in Medicago [40].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the GABA shunt pathway have shown that its function is required for proper growth in response to abiotic stresses [76]. GABA is the product of glutamate decarboxylase, and thus its abundance reflects the activity of GAD [77]. Xu reported that GABA metabolism is a novel mechanism to improve plant stress resistance [78].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gamma-aminobutyric acid in soybean increased with PDS solution alone ( Figure 7 B). Wheats responded to drought stress during the seedling stage, which related to reactive oxygen species scavenging systems and the activation of antioxidant enzymes, which were associated with activation of the gamma-aminobutyric acid shunt pathway and its production [ 58 ]. Additionally, the sonication or hydropriming treatments significantly improved the germination performance of wheat and enhanced gamma-aminobutyric acid metabolism to maintain the C:N metabolic balance under cold stress [ 59 ].…”
Section: Discussionmentioning
confidence: 99%